Specialized Vasculature in the Rostral Migratory Stream as a Neurogenic Niche and Scaffold for Neuroblast Migration. Issue 3 (March 2015) - Yuan, Ti-Fei; Liang, Yu-Xiang; Tay, David; So, Kwok-Fai; Ellis-Behnke, Rutledge
Neurovascular niches serve as the hosts for adult neural stem cells in both the hippocampus and subventricular zone. The rostral migratory stream (RMS) vasculature has been found to be important for neuroblast migration, while its roles in hosting putative neural stem cells have not been investigated. Here we investigated the organization of RMS vasculature and its contribution to the production of new neurons. A single pulse of bromodeoxyuridine (BrdU) administration revealed locally formed new neurons within RMS were located adjacent to blood vessels. In addition, BrdU label-retaining cells that are putative neural stem cells were also found close to the vasculature. Sodium fluorescein perfusion assay demonstrated that the blood-brain barrier (BBB) organization was especially "leaky" in the neurogenic niches. Immunohistochemical visualization of some BBB component molecules indicated a thinner BBB in the RMS region, compared to that in the frontal cortex of adult rats. Finally, the expression of vascular endothelial growth factor was strong and specialized in the RMS region, implying that the region was active in cell proliferation and migration. Here we show that the RMS vasculature associated with surrounding astrocytes provides a highly organized neurovascular niche for adult neural stem cell proliferation, in addition to the function of neuroblast migration support. This result points to a new vasculature supporting neurogenic region in the brain.